New Insights into the Structural and Stratigraphic Evolution of the Northern Sumatra Basin, Aceh - Muchlis (Curtin University, 2022)
The Northern Sumatra Basin is a Paleogene-Neogene basin in a back-arc setting relative to the volcanic arc along the Barisan Mountains. The North Sumatra Basin is a prolific hydrocarbon province, evidenced by the giant Arun gas field and other petroleum fields. However, it is underexplored and does not have any new data due to the long periods of domestic war. This thesis investigates the geology of the North Sumatra Basin using existing data.